Estrategias publicitarias en el almacén “Área Íntima” en el cantón Babahoyo periodo 2021. - Herrera Coronel, Fernanda Michelle (2022)
This case study is being carried out with the purpose of publicizing the advertising strategies to implement them in the "Intimate Area" store in the city of Babahoyo. Given that the market is wide in terms of the sale of intimate apparel, the actions developed in this plan seek to face the difficulties that the competitive market presents and thus be able to remain in the mind of the consumer for a long time and achieve a greater number of clients. In this investigation, the technique of interviewing the manager was used, with a duly elaborated 10-question questionnaire, the results of which provide very valuable basic information for making decisions in the elaboration of an advertising strategy plan.